A splash-reducing clinical handwash basin reduces droplet-mediated dispersal from a sink contaminated with Gram-negative bacteria in a laboratory model system. (August 2021) - Aranega-Bou, P.; Cornbill, C.; Verlander, N.Q.; Moore, G.
Summary: Infection prevention strategies need to be identified and evaluated to reduce the risk associated with contaminated hospital sinks. This study used settle plates to compare the dispersal of Gram-negative bacteria from a conventional, rear-draining clinical handwash basin (CHWB) and a 'splash-reducing' CHWB with and/or without impaired drainage. Two scenarios were assessed: dispersal from a contaminated basin and dispersal from a contaminated drain. The associated tap was operated for 1 min and, for all contamination scenarios, the 'splash-reducing' CHWB had significantly lower odds of spreading contamination than the conventional CHWB.